Implementasi Kebijakan Pengelolaan Pertamanan di Kota Palangka Raya Provinsi Kalimantan Tengah: Implementation of Park Management Policies in Palangka Raya City, Central Kalimantan Province - Pahlawan, Reza; Andrean, Edy (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2015)
This study aims to find out and describe the implementation of garden management policies in the City of Palangka Raya through Regional Regulation No. 03 of 2006 in order to create useful gardening conditions. The research method used is descriptive qualitative. In this case, the researcher wants to describe and also explain the phenomena that occur related to gardening problems that are still lacking in management. The primary data source of this research is the people of the City of Palangka Raya and the Office of Cipta Karya, Spatial Planning and Housing. The results of this study address this shows that there is still low awareness and willingness of the community to participate together in maintaining and managing parks. In addition, the communication, supervision and human resources factors that are owned by the related Office as the implementation of the policy to the public is felt to have not run optimally